The diverse roles of RIP kinases in host-pathogen interactions (2020)
Receptor Interacting Protein Kinases (RIPKs) are cellular signaling molecules that are critical for homeostatic signaling in both communicable and non-communicable disease processes. In particular, RIPK1, RIPK2, RIPK3 and RIPK7 have emerged as key mediators of intracellular signal transduction including inflammation, autophagy and programmed cell death, and are thus essential for the early control of many diverse pathogenic organisms. In this review, we discuss the role of each RIPK in host responses to bacterial and viral pathogens, with a focus on studies that have used pathogen infection models rather than artificial stimulation with purified